2016
DOI: 10.1152/japplphysiol.00860.2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating countermeasures in spaceflight analogs

Abstract: Countermeasures are defined as solutions to prevent the undesirable physiologic outcomes associated with spaceflight. Spaceflight analogs provide a valuable opportunity for the evaluation of countermeasures because they allow for the evaluation of more subjects, more experimental control, and are considerably less expensive than actual spaceflight. The various human analogs have differing strengths and weaknesses with respect to the development and evaluation of countermeasures. The human analogs are briefly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The bed rest experimental model, initially established as an earth-based analog to explore the effects of space-travel related microgravity ( Deitrick et al, 1948 ), is especially valuable as it provides a unique insight into the integrative physiological deconditioning in response to whole body unloading. Bed rest investigations that were performed over the last half-century clearly showed that whole body inactivity generally provokes muscle atrophy of the lower limbs at an initial rate of about 2–3% per week ( Pavy-Le Traon et al, 2007 ; Narici and de Boer, 2011 ; Ploutz-Snyder, 2016 ). Thus, previous work suggests that a ∼7–12% reduction of the thigh and calf muscle mass can be expected following 3 weeks of bed rest-induced inactivity ( Kawakami et al, 2000 , 2001 ; Akima et al, 2001 ; Kubo et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bed rest experimental model, initially established as an earth-based analog to explore the effects of space-travel related microgravity ( Deitrick et al, 1948 ), is especially valuable as it provides a unique insight into the integrative physiological deconditioning in response to whole body unloading. Bed rest investigations that were performed over the last half-century clearly showed that whole body inactivity generally provokes muscle atrophy of the lower limbs at an initial rate of about 2–3% per week ( Pavy-Le Traon et al, 2007 ; Narici and de Boer, 2011 ; Ploutz-Snyder, 2016 ). Thus, previous work suggests that a ∼7–12% reduction of the thigh and calf muscle mass can be expected following 3 weeks of bed rest-induced inactivity ( Kawakami et al, 2000 , 2001 ; Akima et al, 2001 ; Kubo et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Space agencies are thus investigating adverse health effects of long-term missions and their possible countermeasures in order to reduce detrimental consequences for astronaut health (Aubert et al, 2016 ; Bergouignan et al, 2016 ; Frippiat et al, 2016 ; White et al, 2016 ; Lang et al, 2017 ). Space analogs simulating prolonged gravity changes therefore play a crucial role (Ploutz-Snyder, 2016 ). Bed rest with −6 degrees head-down tilt (HDT) is one of the best conditions to mimic the effect of long-term weightlessness on the human body—even within the limitations of this model.…”
Section: Introductionmentioning
confidence: 99%
“…Despite research spanning at least four decades on weightlessness-associated cardiovascular alterations (Pavy-Le Traon et al, 2007 ; Hargens and Vico, 2016 ), the exact time courses of changes in hemodynamic regulation and autonomic cardiovascular control induced by long-term spaceflight are not fully understood (Liu et al, 2015 ; Aubert et al, 2016 ). Moreover, several countermeasures for cardiovascular deconditioning have already been tested (e.g., volume loading, lower-body negative pressure, hypergravity; Wang et al, 2011 ; Stenger et al, 2012 ; Jeong et al, 2014 ; Li et al, 2017 ), but exercise is the most investigated countermeasure (Blaber et al, 2009 ; Petersen et al, 2016 ; Ploutz-Snyder, 2016 ). However, despite the consensus on physical activity as a countermeasure, the type and intensity of the exercise are undergoing further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is little or no genetic memory in organisms on how to respond to force changes in the low gravity range. Hence, it is likely that terrestrial life adapting to µ g will reveal many novel mechanisms that could be helpful in biomedical research [ 8 , 9 , 10 ].…”
Section: Learning From Spacementioning
confidence: 99%